Persuasive strategies in Buhari's maiden coup speech - Tanko, Abubakar Musa; Ismail, Muhd Zulkifli; Abdul Jabar, Mohd Azidan; Mustapha, Nik Farhan (Human Resource Management Academic Research Society, 2021)
Remarkable leaders are those who are skilled at communicating their ideas with a good sense of persuasion. The present paper attempts to investigate the Linguistic augmentative means and devices of the Nigerian President, Muhammadu Buhari, regarding his speech Save Our Great Nation from Total Collapse (1984). In order to analyse the speech, Johnstone's (2008) framework for persuasive strategies was used. The findings demonstrate the use of three persuasive strategies: quasi-logical, presentational and analogical. Quasi-logical argumentation, which is based on rationality, was made through syllogism, enthymeme, and causation. Second, president Muhammadu Buhari manipulated presentational persuasion via rhetorical deixis, metaphors, images, and similes to create involvement. Finally, attempting to elevate the spiritual values of his addressees regarding the cause of their being in the economic impasse under corrupt leadership and to motivate his audience to receive his claims about the outgoing government, Buhari employed analogical persuasion by referring to the Holy Qur'an. Of these three strategies, presentational strategies were the most manipulated by President Buhari in the given speech to move his audience and win their support, solidarity, and cooperation for his plans.